English for specific technical and engineering academic purposes: An analysis on ESL practitioners’ challenges - Nor Yazi Khamis; Azwin Arif Abdul Rahim; Supyan Hussin (International Journal of Evaluation and Research in Education (IJERE), 2019)
The facilitation of English for Specific Engineering Academic Purposes approach at Malaysian technical and engineering tertiary institutions is an effort to revitalise the pedagogical methods of ESL learning and communication skills at the institutions. A close examination on the ESL practitioners’ context has indicated a critical gap between the diversified requirements of skills and sound pedagogical models to determine the practitioners’ quality. In understanding the necessity of the approach, this study aims to explore and investigate the challenges faced by the practitioners in facilitating the approach. The study comprised data gathered from semi structured interviews of 14 ESL experts and an online survey on 42 ESL practitioners in technical and engineering fields. Interview questions for the experts were developed to find out about the challenges and competencies to overcome the hurdles. A self-assessed instrument with a five-Likert scale of importance on the competencies was used to gauge the practitioners’ view onn the approach. Frequencies and percentages, and Braun and Clarke’s (2006) six-stage method of thematic analysis were used to analyse the data. Findings from the both inquiries revealed several challenges which led to the necessity of wider knowledge and understanding of the approach and the prevalent of specific competencies for the practitioners in overcoming the challenges. The practitioners’ competency was substantially indispensable because it could affect their learners’ interest in learning the skills as well as in understanding the content subject.quality agencies to review and specify the requirement and guideline for ESL practitioners specifically those at technical and engineering tertiary institutions.